Narratives of adolescent women athletes' body self-compassion, performance and emotional well-being. Issue 2 (14th March 2020) - Eke, Abimbola; Adam, Margo; Kowalski, Kent; Ferguson, Leah
ABSTRACT: Sport participation can be a highly rewarding experience for young women. However, it can also involve unpleasant experiences such as failing to meet performance goals and threats to body image, which may detrimentally impact athletes' well-being. Body image is salient for women in sport and can also be a source of suffering/challenge. Treating oneself with compassion has been suggested as a resource to buffer against negative outcomes of failure and inadequacy in sport. Body self-compassion may be especially relevant in sport as it consists of a kind and non-judgmental attitude towards the body despite perceived physical imperfections. The purpose of this study was to explore the role of body self-compassion in adolescent women athletes' performance perceptions and emotional well-being. Seven women athletes (14–17 years old) participated in two, one-on-one semi-structured interviews and a journaling activity. Interviews and journal data were analyzed using a holistic approach to thematic analysis. Four themes were developed that capture the athletes' perceived role of body self-compassion: (a) Compassion for and confidence in my body, (b) " Their' thoughts and my body, (c) I will play to my potential, and (d) My strength is in my emotions . The women athletes explained that body self-compassion allows them to respect and treat their bodies with kindness; thus, positive emotions such as satisfaction with the body were strengthened and an adaptive focus placed on performance. These findings are consistent with the conceptualization of self-compassion and body self-compassion and suggest that being body self-compassionate may regulate emotions and sport performance perceptions.